Food chemistry under high hdydrostatic pressure - Butz, Peter (High pressure food science, bioscience and chemistry, 1998)
Foods pasteurized by hydrostatic high pressure have already been marketed in Japan. There is great interest in this method also in Europe and USA. Tem…